Modification of erythrocyte membrane phospholipid composition in preterm newborns with retinopathy of prematurity: The omegaROP study - Karadayi, Rémi; Pallot, Charlotte; Cabaret, Stéphanie; Mazzocco, Julie; Gabrielle, Pierre-Henry; Semama, Denis S.; Chantegret, Corinne; Ternoy, Ninon; Martin, Delphine; Donier, Aurélie; Gregoire, Stéphane; Creuzot-Garcher, Catherine P.; et al. (Frontiers in Cell and Developmental Biology, 2022)
N-3 polyunsaturated fatty acids (PUFAs) may prevent retinal vascular abnormalities observed in oxygen-induced retinopathy, a model of retinopathy of prematurity (ROP). In the OmegaROP prospective cohort study, we showed that preterm infants who will develop ROP accumulate the n-6 PUFA arachidonic acid (ARA) at the expense of the n-3 PUFA docosahexaenoic acid (DHA) in erythrocytes with advancing gestational age (GA). As mice lacking plasmalogens ―that are specific phospholipids considered as reservoirs of n-6 and n-3 PUFAs― display a ROP-like phenotype, the aim of this study was to determine whether plasmalogens are responsible for the changes observed in subjects from the OmegaROP study. Accordingly, preterm infants aged less than 29 weeks GA were recruited at birth in the Neonatal Intensive Care Unit of University Hospital Dijon, France. Blood was sampled very early after birth to avoid any nutritional influence on its lipid composition. The lipid composition of erythrocytes and the structure of phospholipids including plasmalogens were determined by global lipidomics using liquid chromatography coupled to high-resolution mass spectrometry (LC-HRMS). LC-HRMS data confirmed our previous observations by showing a negative association between the erythrocyte content in phospholipid esterified to n-6 PUFAs and GA in infants without ROP (rho = -0.485, p = 0.013 and rho = -0.477, p = 0.015 for ethanolamine and choline total phospholipids, respectively). Phosphatidylcholine (PtdCho) and phosphatidylethanolamine (PtdEtn) species with ARA, namely PtdCho16:0/20:4 (rho = -0.511, p < 0.01) and PtdEtn18:1/20:4 (rho = -0.479, p = 0.015), were the major contributors to the relationship observed. On the contrary, preterm infants developing ROP displayed negative association between PtdEtn species with n-3 PUFAs and GA (rho = -0.380, p = 0.034). They were also characterized by a positive association between GA and the ratio of ethanolamine plasmalogens (PlsEtn) with n-6 PUFA to PlsEtn with n-3 PUFAs (rho = 0.420, p = 0.029), as well as the ratio of PlsEtn with ARA to PlsEtn with DHA (rho = 0.843, p = 0.011). Altogether, these data confirm the potential accumulation of n-6 PUFAs with advancing GA in erythrocytes of infants developing ROP. These changes may be partly due to plasmalogens.